2002
DOI: 10.1186/1472-6815-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Weather conditions and sudden sensorineural hearing loss

Abstract: BackgroundClimatic or meteorological condition changes have been implicated in the pathogenesis of Idiopathic Sudden Sensorineural Hearing Loss (ISSHL). We investigated the seasonal distribution of ISSHL and evaluated the influence of meteorological parameters (such as temperature, humidity, and atmospheric pressure), their variation and covariation on the incidence of the disease.MethodsA total of 82 cases of ISSHL, admitted to our department over a five-year period, were enrolled in the study. Seasonal distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
1
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 15 publications
3
32
1
4
Order By: Relevance
“…This finding is consistent with the study by Megighian et al [19 ]which concluded that cases of SSNHL tended to be cyclical in any given year[.] However, the study by Danielides et al [15 ]failed to observe any significant relationship between seasons and the incidence of SSNHL.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding is consistent with the study by Megighian et al [19 ]which concluded that cases of SSNHL tended to be cyclical in any given year[.] However, the study by Danielides et al [15 ]failed to observe any significant relationship between seasons and the incidence of SSNHL.…”
Section: Discussionsupporting
confidence: 80%
“…We find that the annual SSNHL incidence rates in Taiwan ranged between 6.49 and 10.21 per 100,000, which is comparable with the previously reported annual SSNHL incidence rates of 5–20 per 100,000 in the US [4] and the 10.25 per 100,000 found in the Prefecture of Ioannina in Greece between 1995 and 1999 [15]. They are also in line with the findings on Japan of 6.30 per 100,000 in 1987, and 10.3 per 100,000 in 1993 [13].…”
Section: Discussionsupporting
confidence: 78%
“…However, whilst the studies of Danielides et al [2002] in Greece, Preyer [1996] in Germany and Mizukoshi et al [1995] in Japan have consistently reported that no relationship exists between climate and the onset of SSNHL, the studies undertaken in Germany by Mees et al [1987] and Herbert et al [1987] have reported a signifi cant relationship between the onset of SSNHL and weather. A possible explanation for this discrepancy may be that the earlier studies have tended to rely upon regional samples, or on data from only a few selected hospitals or subpopulations of patients, each of which would not be suffi ciently representative to permit unequivocal conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The fi ndings of those studies which have focused on these factors have been somewhat varied, with some reporting a relationship between the incidence of SSNHL and atmospherics [Mees et al, 1987], while others have failed to establish any relationship whatsoever between the incidence of SSNHL and meteorological parameters [Danielides et al, 2002;Preyer, 1996;Mizukoshi et al, 1995]. Furthermore, these studies have also tended to rely heavily upon data from a few selected hospitals, or from subgroups of populations, which may well account for the inconsistencies across the various studies.…”
mentioning
confidence: 99%
“…Many studies have been carried out to investigate associations with climate and season. Danielides et al [2002] compared the differences in the incidence of SSNHL depending on the temperature, atmospheric pressure, and humidity among 82 SSNHL patients, but found no significant correlations. Jourdy et al [2010] also reported that there was no difference in the monthly incidence among patients with SSNHL in a tertiary care center in New York, NY, USA.…”
Section: Discussionmentioning
confidence: 99%